Management of safflower aphid (Uroleucon compositae) through newer insecticides: MANAGEMENT OF SAFFLOWER APHID THROUGH NEWER INSECTICIDES - V B AKASHE; D V INDI; D R MURUMKAR; S V KHADTARE; S K SHINDE (Journal of Oilseeds Research, 2020)
A field experiment was conducted for three years during rabi 2013-14 to 2015-16 to evaluate the efficacy and compatibility of insecticides, fungicides and bio-agents for the management of the insect pest, aphid (Uroleucon compositae) and the diseases like Alternaria leafspot and Fusarium wilt in safflower. The pooled data of three years showed significant reduction in aphid infestation in terms of number of aphids per 5 cm apical twig in all the treatments in comparison with the absolute control. The extent of aphid control in different treatments ranged from 70.2 to 88.0% after first spray and from 81.6 to 91.4% after second spray. Thus, all the treatments were capable of keeping the aphid population below the ETL level (35-40/5cm apical twig). There was no notable buildup of Alternaria leaf spot as the crop was sown during the normal recommended time. The Fusarium wilt incidence was also less which ranged from 1.2 to 7.6%. All the treatments recorded significant improvement in yield over the absolute control but they were at par with each other. However, the highest average seed yield of 907 kg/ha was recorded by T5 (Spray of thiamethoxam @ 0.25 g/l). The seed yield in other treatments ranged from 801 to 875 kg/ha as against only 292 kg/ha in the absolute control. The benefit-cost analysis of the treatments showed that the treatment T5 recorded the highest B:C ratio of 2.06 followed by T6 (1.94), T7 (1.89), T4 (1.62), T2 (1.44), T1 (1.40) and T3 (1.39). There was no phytotoxic effect on safflower crop in any of the treatments involving combination of different insecticides, fungicides and bio-agents. Therefore, seed treatment with T. asperellum TaDOR 7316 @ 10 g/kg and tank mixing of insecticides and fungicides together for need-based pest and disease management in safflower is recommended.